Diversity in career orientation at the polytechnic school: Do textbooks take the diversity of students into account? - Berger, Georg (Momentum Quarterly, 2024)
The polytechnic school (PTS) was established by law in Austria in 1962 in connection with the extension of compulsory schooling to nine years in the education system and started in the school year 1966/67. As a compulsory type of pre-vocational school, it is primarily intended for those students who wish to pursue an apprenticeship, but it is also possible to continue attending a secondary school. The PTS therefore has an important function in terms of vocational and educational orientation. This raises the question of the extent to which stereotypes are reproduced or challenged. As the PTS is characterised by a high degree of cultural diversity in terms of migration background, especially in urban areas, the current question is whether and how this is taken into account. One empirical indicator of this is the representation of young people, their interests and career aspirations in textbooks. In summary, it can be said that the gender debate has been well addressed, while there is still some catching up to do in terms of diversity.
Keywords: Diversity; intersectionality; migrant background; gender allocation; polytechnic school (PTS)